The Healing Nature of Occupation - Jennifer Fortuna (Scholarworks @ WMU, 2017)
Moses Hamilton, an artist based in Hawaii, provided the cover art for the Spring 2017 edition of The Open Journal of Occupational Therapy (OJOT). "Pali Kai" is a 11"x14" painting made from acrylic on canvas. When a tragic car accident left Hamilton paralyzed from the chest down, mouth painting provided an outlet for selfexpression and stress relief. Participation in a meaningful occupation helped Hamilton find his path in life. With their colorful impressionist-style, Hamilton's paintings have brought happiness to people all over the world.